Factors associated with electrical stimulation‐induced performance fatigability are dependent upon stimulation location. Issue 4 (9th March 2021) - Inns, Thomas B.; McCormick, Daniel; Greig, Carolyn A.; Atherton, Philip J.; Phillips, Bethan E.; Piasecki, Mathew
Abstract : New Findings: What is the central question of this study? How does peripheral nerve stimulation (PNS) compare with neuromuscular electrical stimulation (NMES) used clinically to reduce muscle atrophy? What is the main finding and its importance? NMES resulted in progressive increases in M‐wave duration and delay of muscle relaxation throughout a single stimulation protocol, findings not observed with PNS. This suggests PNS recruits from a wider pool of muscle fibres/motor units, providing a more favourable alternative to NMES for rehabilitation intervention. Abstract: Neuromuscular electrical stimulation (NMES) is increasingly viewed as a central tenet to minimise muscle loss during periods of disuse/illness – typically applied directly over a muscle belly. Peripheral nerve stimulation (PNS) is afforded less attention, despite providing a more global contractile stimulus to muscles. We investigated NMES versus PNS in relation to performance fatigability and peripheral contributions to voluntary force capacity. Two fatigue protocols were assessed separately: (1) over‐quadriceps NMES and (2) peripheral (femoral) nerve stimulation (PNS). Before and after each session, a maximal voluntary contraction (MVC) was performed to assess force loss. Knee‐extensor force was measured throughout to assess contractile function in response to submaximal electrical stimulation, and M‐wave features quantified myoelectrical activity. NMES and PNS induced similar voluntary (MVC, NMES: −12 ± 9%, PNS: −10 ± 8%, both P  < 0.001) and stimulated (NMES: −45 ± 12%, PNS −27 ± 27%, both P  < 0.001) force reductions. Although distinct between protocols, myoelectrical indicators of muscle recruitment (M‐wave area and amplitude) and nerve conduction time did not change throughout either protocol. Myoelectrical propagation speed, represented as M‐wave duration, and the delay before muscle relaxation began both progressively increased during NMES only ( P  < 0.05 and P  < 0.001, respectively). NMES myoelectrical changes suggested performance fatigability, indicating activation of superficial fibres only, which was not observed with PNS. This suggests PNS recruits a wider pool of muscle fibres and motor units and is a favourable alternative for rehabilitation. Future work should focus on implementing PNS interventions in clinically relevant scenarios such as immobilisation, care homes and critical illness. Abstract :